Characteristics of a dual-broadband antenna with crossed elliptical probes and L-shaped slits - Khoomwong, Ekajit; Phongcharoenpanich, Chuwong (My University, 2017)
Characteristics of a dual broadband antenna are investigated. The antenna consists of crossed elliptical probes, L-shaped slits, and split circular ground-planes. The proposed antenna covers various widely-employed frequency standards: IEEE 802.11b/g/n, IEEE 802.16, GSM, UMTS and LTE. The design and investigation are based on numerical simulations. The dual broad-bandwidths are 1.46 GHz (1.69-3.15 GHz) and 1.69 GHz (4.93-6.62 GHz), which simultaneously cover the above-mentioned frequency standards. The radiation patterns are of conical-beam type with peak gains of 3.1 and 5.1 dBi at 2.45 and 5.5 GHz, respectively. It has the advantage of main-beam directions pointing to nearly the same tilt angle for both main operating bands, which can be very useful for ceiling-mounted installations and simultaneous dual-band operations.
Keywords: broadband antenna; crossed elliptical probe; dual band; L-shaped slit